The Interactive Model of L2 Listening Processing in Chinese Bilinguals: A Multiple Mediation Analysis - Yang, Yilong; Yang, Guoying; Li, Yadan (Frontiers in Psychology, 2022)
Second language (L2) listening is a common challenge for language learners. It remains largely unknown that how bilinguals process L2 listening. The literature has suggested an interactive model of L2 listening processing. However, few studies have examined the model from an experimental approach. The current study tried to provide empirical evidence for the interactive model of L2 listening processing in bilinguals by exploring the relationships among English spoken word segmentation (SWS), cognitive inhibition, cognitive flexibility, and L2 listening proficiency. The results showed that there were positive associations among SWS, cognitive inhibition, cognitive flexibility, and L2 listening proficiency. Mediation analysis suggested that SWS had a positive influence on L2 listening proficiency both directly and indirectly through cognitive inhibition and cognitive flexibility respectively. These results imply that both bottom-up (reflected at SWS) and top-down (reflected at cognitive inhibition and flexibility) processes are engaged in bilinguals’ L2 listening processing.